Using Macro Flash Animation Media on Motion Material to Improve Learning Achievement for Learning Science in Junior High School - Saripudin, Endang; Sari, Indah Juwita; Mukhtar, Mukhtar (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
This research was conducted to improve students' ability in learning of motion material at one of the junior high school in Serang, Indonesia. The hypothesis of action to be tested is the achievement of learning of motion material can be increased through macro flash animation media in learning process. This research involved students of class VIII B as many as 33 people. Data were collected through the instrument, direct observation in the field and generate initial data of student’s ability or pre-cycle in the material motion 63.03 (less categories). The objectives of this research are: (1) to improve student's learning motivation in motion system concept by using simple props, (2) to improve student learning outcomes through classroom action research with several cycles. Based on the observation, the causes of low comprehension and student learning outcomes on the concept of motion are: (1) low student motivation, (2) inadequate learning infrastructure, (3) teachers do not vary in providing learning media. Then, based on observation and the results of pre-cycle, then conducted research with activity 2 cycles where the cycle to 1 shows the results increased to 69.70 (good category) and in the second cycle to 83.79 (very well category). Thus, the success indicator is achieved so that the approach by using animation media macro flash as a simple tool can improve student's motivation and achievement, both in present and future.